STRATEGI PARTAI KEADILAN SEJAHTERA (PKS) UNTUK MEMENANGKAN CALON KEPALA DAERAH YANG DIUSUNGNYA DI KABUPATEN PADANG LAWAS UTARA - GUSTIAR HAMONANGAN (Institut Agama Islam Negeri Padangsidimpuan, 2017)
This research focused on Strategi Partai Keadilan Sejahtera (PKS) Untuk Memenangkan Calon Kepala Daerah Yang Diusungnya di Kabupaten Padang Lawas Utara. The problems of this research was to know how Partai Keadilan Sejahtera (PKS) won the candidate for regional head who their carried and what their problems. Elections are the first step for political parties to compete for power to occupy executive or legislative seats. Political parties and candidates need to think the strategies that can determine the victory to win the seat of power. It likes Partai Keadilan Sejahtera who carried the candidate for regional head in Kabupaten Padang Lawas Utara. The objectives of the research: (1) to know the strategy used by Partai Keadilan Sejahtera (PKS) in regional head election in Kabupaten Padang Lawas Utara, (2) to know the problems faced by Partai Keadilan Sejahtera (PKS) in applying the strategy in regional head election in Kabupaten Padang Lawas Utara. This research is qualitative research. It was located at DPD office Partai Keadilan Sejahtera. The data was collected through interview of administer DPD (Dewan Pengurus Daerah) Partai Keadilan Sejahtera Kabupaten Padang Lawas Utara. Besides, it is used data and document to support the information needed. The result of this research shows that there are some strategies used by Partai Keadilan Sejahtera (PKS) and problems which were faced by them. he strategies are by doing service to community, socialization in conveying the vision and mission of candidate pair, campaign, doing event, and apply Islamic ideology. The problem includes less coordination from candidate to party their carried